Effective-mononuclear cell (E-MNC) therapy alleviates salivary gland damage by suppressing lymphocyte infiltration in Sjögren-like disease - Hasegawa, Kayo; Raudales, Jorge Luis Montenegro; I, Takashi; Yoshida, Takako; Honma, Ryo; Iwatake, Mayumi; Tran, Simon D.; Seki, Makoto; Asahina, Izumi; Sumita, Yoshinori (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Sjögren syndrome (SS) is an autoimmune disease characterized by salivary gland (SG) destruction leading to loss of secretory function. A hallmark of the disease is the presence of focal lymphocyte infiltration in SGs, which is predominantly composed of T cells. Currently, there are no effective therapies for SS. Recently, we demonstrated that a newly developed therapy using effective-mononuclear cells (E-MNCs) improved the function of radiation-injured SGs due to anti-inflammatory and regenerative effects. In this study, we investigated whether E-MNCs could ameliorate disease development in non-obese diabetic (NOD) mice as a model for primary SS. Methods: E-MNCs were obtained from peripheral blood mononuclear cells (PBMNCs) cultured for 7 days in serum-free medium supplemented with five specific recombinant proteins (5G culture). The anti-inflammatory characteristics of E-MNCs were then analyzed using a co-culture system with CD3/CD28-stimulated PBMNCs. To evaluate the therapeutic efficacy of E-MNCs against SS onset, E-MNCs were transplanted into SGs of NOD mice. Subsequently, saliva secretion, histological, and gene expression analyses of harvested SG were performed to investigate if E-MNCs therapy delays disease development. Results: First, we characterized that both human and mouse E-MNCs exhibited induction of CD11b/CD206-positive cells (M2 macrophages) and that human E-MNCs could inhibit inflammatory gene expressions in CD3/CD28- stimulated PBMNCs. Further analyses revealed that Msr1-and galectin3-positive macrophages (immunomodulatory M2c phenotype) were specifically induced in E-MNCs of both NOD and MHC class I-matched mice. Transplanted E-MNCs induced M2 macrophages and reduced the expression of T cell-derived chemokine-related and inflammatory genes in SG tissue of NOD mice at SS-onset. Then, E-MNCs suppressed the infiltration of CD4-positive T cells and facilitated the maintenance of saliva secretion for up to 12 weeks after E-MNC administration. Discussion: Thus, the immunomodulatory actions of E-MNCs could be part of a therapeutic strategy targeting the early stage of primary SS.